CoLiTecVS – A new tool for the automated reduction of photometric observations. Issue 1 (28th March 2019) - Kudzej, I.; Savanevych, V. E.; Briukhovetskyi, O. B.; Khlamov, S. V.; Pohorelov, A. V.; Vlasenko, V. P.; Dubovský, P. A.; Parimucha, Š.
Abstract : The capabilities of telescopes allow the plotting of light curves a routine task. This one shifts the main attention of the astronomer from plotting to research. To achieve this goal, we developed a new tool for the automated reduction of photometric observations, which includes the computational method for the brightness assessment of the investigated and comparison stars, brightness equalization of astronomical images using an inverse median filter, as well as light curve plotting and processing using different tools.